2015
DOI: 10.5582/ddt.2015.01022
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation and <i>in vitro</i> antioxidant activities of a new heteropolysaccharide from <i>Litchi chinensis </i>

Abstract: Two polysaccharides, LCP70S-1 and LCP70W, were isolated from the pulp tissues of Litchi chinensis by anion-exchange chromatography and gel-filtration chromatography, while the structure of LCP70S-1 was elucidated and its physico-chemical properties was analyzed. The results demonstrated that LCP70S-1 is composed of L-rhamnose, L-arabinose and D-galactose in the ratio of 1.06:6.39:4.21, and the main chain of the heteropolysaccharide possess (1→3,6)-linked galactopyranosyl branches at O-6. The three branches con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The fruit is known for its good taste and nutritional properties [ 3 ]. Recent studies have shown that litchi pulp (mesocarp) contains bioactive compounds, including polysaccharides with strong antioxidant activities [ 6 , 7 ]. In addition, Huang et al have also provided evidence that litchi pulp displays anti-tumor and immunomodulatory effects both in vitro and in vivo [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is known for its good taste and nutritional properties [ 3 ]. Recent studies have shown that litchi pulp (mesocarp) contains bioactive compounds, including polysaccharides with strong antioxidant activities [ 6 , 7 ]. In addition, Huang et al have also provided evidence that litchi pulp displays anti-tumor and immunomodulatory effects both in vitro and in vivo [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This portion is enriched with a blend of components with interesting nutraceutical properties. Specifically, many studies have shown that Litchi pulp contains a great percentage of bioactive polysaccharides with strong antioxidant activity [ 19 , 20 , 21 ]. In addition, these compounds display antitumor and immunomodulatory effects in vitro [ 22 ].…”
Section: Antitumor Properties Of Litchi Pulp-derived Componentsmentioning
confidence: 99%